Analisis Materi Pokok Matematika Kelas III MI/SD - Shindy Lestari (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2020)
Analysis of mathematics subject matter in elementary school is a very important field of study taught at every level of education. The 2013 curriculum separates the field of mathematics studies from themes so that this field of study is a subject that stands alone. Through mathematics subject matter taught in elementary school can train students to think critically, rationally, logically, innovatively so that they have competitiveness. As for the problems discussed from the subject matter in elementary school mathematics which is seen from the suitability of the teacher's book and the student's book, in this case it discusses: 1) the scope of mathematics material grade 3rd elementary school, 2) the characteristics of mathematics subject matter in elementary school, 3) the relevance in elementary school mathematics subject matter to the scientific structure, namely student character, HOTS, 4C skills, literacy numeracy, digital literacy, financial literacy and character education, 4) learning innovation based on integration-interconnection in accordance with the science of development and technology and the needs of the community in the Industrial Revolution Era 4.0.